Peningkatan Partisipasi Siswa SMA Negeri 2 Parepare di Ruang Digital dalam Merespons Degradasi Lingkungan - Ridwan Syam; Muh. Iqbal Latief; Ria Renita Abbas; Mutahharah Nemin Kaharuddin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance high school students' participation in responding to environmental degradation through digital platforms at SMAN 2 Parepare. The Participatory Action Research (PAR) method was applied to 25 students from grades XI and XII through a digital environmental education workshop that integrated environmental sociology concepts with Parepare's local realities. The program covered material on environmental crises, Generation Z's role as change agents, digital documentation techniques, and the ENGAGE Framework (Educate-Network-Generate-Amplify-Go Offline-Evaluate) for systematic environmental action. Evaluation using pre-test and post-test showed significant improvement in participants' understanding from an average score of 5.8 to 9.2 (scale of 10). A paradigm shift occurred from passive information consumers to potential active content creators, with 80% of participants reporting increased confidence in creating environmental content and 56% having formulated concrete action plans. The program successfully bridged the gap between theoretical knowledge and practical application, proving that high school students as digital natives have great potential to become environmental change agents when equipped with appropriate knowledge and systematic action frameworks, contributing to achieving Parepare City's sustainable development targets.